Digitalisasi UMKM melalui Pendaftaran NIB dan Pemanfaatan Google Maps Sebagai Media Promosi - Al Arif, Muhammad Arham; Prastya, Angga; Ramadhan, Mohammad Azril; Hartanto, Imani; Thariq, Muhammad Abil; Sefia, Vema; Rahmawati, Yulia; Priyandita, Siska Ayu; Putri, Arma Luthfiana; Zain, Farah Meliani Mahardya; Khusna, Hifa Zaimatul; Chandani, Laksmiatin Zulfa; Hamidah, Siti Sofia; Yulianingrum, Anggraita; Humairoh, Durorin; Ridho, Farah Abidah Iliyina; Mas’udah, Husna Zuhrotul (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This community service project addresses the issue of low understanding among Micro, Small, and Medium Enterprises (MSMEs) in Mojoayu Village, Plemahan District, Kediri Regency, regarding the importance of business legality through a Business Identification Number (NIB) and the optimization of digital promotion through Google Maps. The lack of digital literacy causes obstacles in NIB registration and the use of online promotional media. This research uses the Asset-Based Community Development (ABCD) method, which focuses on strengthening the existing potential of MSMEs, such as skills, networks, and technological devices. The stages include discovery, dream, design, delivery, and destiny. The results of the assistance show that out of ten partner MSMEs, eight successfully obtained an NIB and all of them are registered on Google Maps. This program had a positive impact on increasing business visibility, brand awareness, and business actors' understanding of legality and digital marketing. This assistance model can be replicated for MSME development in other regions.